Περιαυτολογία: um estudo exegético-teológico de Fl 1,12-26 - Auma, Paul Okoth (2017)
This exegetical-theological investigation under the synchronic aspect has as general objective to analyze and verify how the resource of the periautology present in the epistle to the Philippians contributes to the understanding of the discipleship described by the writer throughout his missionary journey. The study seeks to present, specifically, the excerpts with periautological expressions in order to understand the reason why Paul insists on the apparently rhetorical expressions. This research intends to analyze the expressions, to elucidate the rhetorical situations of the resource, and to compare other pericopes that present the same rhetorical style. To begin with, a general survey of the letter is conducted, discussing the perennial questions in an updatedmanner. The hypotheses about the recurring polemics about the place where the letter was written, the question of the date of the writing, and the question of its unity will be confronted. The research aims to explain the question of periautology focusing on the mimesis of the model disciple. Furthermore, it seeks to investigate and present the theological consequences arising from the phrases specifically contained in the pericope of Philippians 1,12-26 to better ground Christian discipleship